Cyclic Variation of Cellular Clock Proteins in the Mouse Estrous Ovary - G Wiggins; M Legge (JRI, 2016)
Background: The mammalian ovary is controlled by a number of biological rhythms, which regulate the recruitment and release of mature oocytes. The main objective of this study was to investigate the role of cellular clock proteins during follicle maturation in the mouse estrous ovary. Methods: Immunohistochemical (IHC) studies were performed on ovaries from 50 estrous staged mice culled at two time points of 09:00 [day] and 01:00 [mid-point of the dark cycle]. Six antibodies were used to identify the expression of core cellular clock proteins (BMAL1, CLOCK, CRY1, CRY2, PER1 and PER2) within the ovary and four follicle stages, primordial, primary, antral and corpus lutea. IHC data was scored using the Allred protocol and significance determined by Mann-Whitney tests. Differences were considered significant at p<0.05. Results: All four follicle stages presented greater BMAL1 and CLOCK protein scores during the day and up regulation of CRY1-2 and PER1-2 at night. In primordial follicles, BMAL1 and CLOCK increases were significant (p<0.05) and CRY-1 and PER-1 were highly significant (p<0.001), and CRY-2 did not reach significance. Primary follicles demonstrated a similar response with BMAL1 and CLOCK, and CRY-1, PER-1-2 all reaching significant expression (p<0.05; p<0.001; p<0.001 respectively). CRY-2 expression was not significant. Antral follicles did not show significant BMAL1 or CLOCK expression, CRY-1 and PER-1 were highly significant (p<0.001) and CRY-2 had a small but significant increase (p<0.05). Corpus lutea demonstrated significant BMAL1 increase but CLOCK had no significant variation. CRY-1, PER1-2 increases were highly significant (p<0.001) and CRY-2 was up regulated but failed to reach significance. Conclusion: The ovary demonstrated a cellular clock response to the light: dark cycle and in addition, as the ovarian follicles mature changes in the positive and negative arms of both clock responsive proteins were observed.